KARAKTERISTIK PATUNG MONUMEN DAN TUGU DI KOTA MEDAN - Tetty Mirwa; Sugito Sugito; Khaerul Saleh; Nelson Tarigan (Gorga : Jurnal Seni Rupa, 2023)
This research was conducted to explore the works of monuments in the city of Medan. This study aims to reveal, explain and document the works of monuments and monuments. Related to this, this research is also: (1) to find out in real terms the techniques, materials of manufacture, visualization of ideas, shape characteristics, and layout arrangements in terms of the observer's perspective on the art of sculpture, monuments, and monuments, (2) to produce teaching materials for Sculpture. with local content in the Department of Fine Arts at the State University of Medan. The study was conducted on a population and a sample of 3 works. Data were collected by using the methods of observation, documentation, and questionnaires. Data analysis was used descriptively and qualitatively with the type of taxonomic analysis. The results of the analysis and discussion conclude that the meaning of monumental sculpture in the city of Medan expresses the value of state ideology, history, and culture. The meaning is contained in the shape, color, size of the material, and the location of the work which is based on the philosophy of Pancasila, the history of struggle, and the culture of the Indonesian nation. While the techniques used were the grain technique and cast iron reinforced concrete, the techniques were also modeling (printing), then the materials used were cement, concrete, and bronze. The average visualization of the work displayed human figures, while the monument displayed rectangular concrete objects towering upwards.Keywords: statues, monuments, teaching materials. AbstrakPenelitian ini dilakukan untuk mendalami tentang karya patung monumen dan tugu yang terdapat di Kota Medan. Penelitian ini bertujuan untuk mengungkapkan, menjelaskan, dan mendokumentasikan karya patung monumen dan tugu. Terkait hal ini, penelitian ini juga adalah: (1) mengetahui secara nyata teknik, bahan pembuatan, visualisasi ide, karakteristik bentuk, pengaturan tata letak ditinjau dari perspektif pengamat pada seni patung monumen dan tugu, (2) menghasilkan bahan ajar Seni Patung yang bermuatan lokal pada Jurusan Seni Rupa di Universitas Negeri Medan. Penelitian dilakukan terhadap populasi dan 3 sampel karya. Pengumpulan data dilakukan dengan menggunakan metode observasi, dokumentasi dan kuesioner. Analisis data digunakan secara deskriptif kualitatif dengan jenis analisis taksonomi. Hasil analisis dan pembahasan menyimpulkan bahwa makna karya seni patung monumen di Kota Medan mengungkapkan nilai pada ideologi negara, sejarah dan budaya. Makna tersebut terkandung pada bentuk, warna, ukuran, bahan dan lokasi karya yang berlandaskan pada falsafah Pancasila, sejarah perjuangan dan budaya bangsa Indonesia. Sedangkan teknik yang digunakan adalah teknik butsir, cor beton bertulang besi, juga teknik modelling (cetak), selanjutnya bahan yang digunakan rata-rata semen beton dan ada perunggu. Rata-rata visualisasi karya menampilkan sosok/figur manusia, sedangkan tugu menampilkan benda bentuk beton persegi panjang menjulang ke atas.Kata Kunci: patung, tugu pengayaan, bahan ajar.Authors:Tetty Mirwa : Universitas Negeri MedanSugito : Universitas Negeri MedanKhaerul Saleh : Universitas Negeri MedanNelson Tarigan : Universitas Negeri MedanReferences:Gie, L. (1976). Garis Besar Estetik. Yogyakarta: UGM.Hoeve, V. W. (1950). Ensiklopedia Indonesia. Bandung: Hoeve Press.Muchtar, B. (1992). Seni Patung Indonesia. Yogyakarta: ISI Yogyakarta.Primadi, P. (1978). Proses Kreasi dan Apresiasi Seni. Jakarta: Ghalia Indonesia.Saylor, H. H. (1952). Dictionary of Architecture. New York: John Wilcy and Son Inc.Sirait, B. (1985). Komposisi Seni Rupa. Medan: IKIP Medan.Soedarso, S.P. (1976). Tinjauan Seni. Yogyakarta: ASRI.Soekadarman, M. S. (1977). Filsafat Seni dan Fenomenologi Karya Seni. Malang. Malang: IKIP Malang.Suryabrata, S. (2012). Metodologi Penelitian. Jakarta: Raja Grafindo Persada.Webster, M. (1971). Webster Seven New Dictionary. New York: G & C Merriam Company.